ANALYSIS OF TECHNICAL EFFICIENCY OF RICE FARMING ON DIFFERENT LAND AREA STRATA IN BENGKULU PROVINCE - Prasania, Maya Dhelima; Sukiyono, Ketut; Romdhon, M. Mustopa (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Efficiency in utilizing production factors in rice farming is measured by assessing technical efficiency. This technical efficiency reflects how well farmers utilize production input factors to produce output. The problem is, to what extent is the level of technical efficiency of lowland rice farming at different strata of land area? The aim of this research is to (a) analyze differences in the level of efficiency of lowland rice farming in different strata of land area in Bengkulu Province, (b) analyze what factors influence lowland rice farming in different strata of land area in Bengkulu Province. This research method is quantitative, and data is collected by distributing questionnaires to 175 farmers in different land strata in Lebong Regency and South Bengkulu Regency. The data were analyzed using the Cobb-Douglas production function with the Stochastic Frontier approach. The research results show that 1) efficiency varies between each stratum of land area, with an average level of efficiency in stratum I of 96.89%, stratum II of 89.14%, stratum III of 98.40%, and in stratum combined 94.81%; 2) The factors that influence the technical efficiency of rice farming in stratum I consisting of land, urea and female labor, in stratum II consisting of seeds and phonska, in stratum III consisting of land area and seeds. Meanwhile, regarding technical inefficiency in rice farming, the influencing factors in stratum I consist of age, education, experience, and number of dependents; in stratum II, it consists of age, while in stratum III, it consists of age, education, and experience.